Uzun Süreli Ranitidin Tedavisi alan Olguda Nondepolarizan Bloker Ajanlara Karşı Rezistans Gelişimi (Olgu Sunumu) - Keleş, Gönül Tezcan; Kara, Eray; Tok, Demet (Fırat University, 2007)
Biz bu yazıda, 65 yaşında, duodenal ülser nedeniyle uzun süredir ranitidine tedavisi gören ve üst gastrointestinal sistem kanaması nedeniyle opere olan erkek olguyu sunduk. Genel anestezi altında opere olan olguda nondepolarizan kas gevseticilerden vekuronium ve mivakuriuma karşı rezistans gelişti. Rezistans oluşturacak mekanizmalar arasında vekuronium ve mivakuriumun ranitidin ile etkileşmesi en büyük olasılıktır. ©2007, Fırat Üniversitesi, Tıp Fakültesi

We report a case of a 65-year-old man with a history of duodenal ulcer that treated preoperatively with ranitidine and underwent surgical exploration for upper gastrointestinal hemorrhage under emergency conditions. Under general anaesthesia, he showed resistance to two nondepolarizing neuromuscular blocking drugs. No obvious cause for the resistance was demonstrated except for the possibility of an interaction between ranitidine with vecuronium and mivacurium. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Resistance to Nondepolarizing Blocking Agents in a Patient Prolonged Treatment with Ranitidine